2019
DOI: 10.3390/f10100881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Strain Rate and Fiber Direction on the Dynamic Mechanical Properties of Beech Wood

Abstract: As a macroscopically orthotropic material, beech wood has different mechanical properties along the fiber direction and the direction perpendicular to the fiber direction, presenting a complicated strain rate sensitivity under impact or blast loadings. To understand the effect of the strain rate on the mechanical properties of beech wood, dynamic compression tests were conducted for the strain rate range of 800 s−1–2000 s−1, and quasi-static compression tests for obtaining the static mechanical properties of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In most of the tests performed, the mechanical properties of the dynamic tests were higher than those of the static tests [32][33][34]. However, even more obvious were the differences between the mechanical properties obtained at very high strain rates and those obtained in the quasi-static tests; the former differences are much higher [35].…”
Section: Introductionmentioning
confidence: 90%
“…In most of the tests performed, the mechanical properties of the dynamic tests were higher than those of the static tests [32][33][34]. However, even more obvious were the differences between the mechanical properties obtained at very high strain rates and those obtained in the quasi-static tests; the former differences are much higher [35].…”
Section: Introductionmentioning
confidence: 90%
“…During Hopkinson or weight-down crushing to assess the effect of the speed of the stress on the behaviour of the wood material [9][10][11][12][13], it was found that the average stress increased with the dynamic effect, causing an increase of the energy absorbed and therefore of the SEA.…”
Section: Comparison Of Static and Dynamic Crushingmentioning
confidence: 99%
“…Johnson analysed the problem in 1986, mainly from a historical point of view in the naval field [8]. Some studies have been carried out to study the dynamic behaviour of wood via tests on Hopkinson bars [9][10][11][12] but few dynamic studies have been carried out on drop weight apparatus. Adalian and Morlier [13], however, studied the behaviour, in the longitudinal and tangential directions, of poplar in the form of massive rectangular specimens with this kind of tests.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Wood produces a series of mechanical relaxation processes at different temperatures, making the mechanical state and the relaxation transition behavior of wood more complicated (Pang et al 2019).…”
Section: Introductionmentioning
confidence: 99%